High Medieval textiles of Asian and Middle Eastern provenance at Prague Castle, Czech Republic - Bravermanová, Milena; Brezinová, Helena; Víchová, Jana Bures (Archaeological Textiles Review, 2020)
A total of 18 medieval textiles produced in Asia and the Middle East were found in the tomb of St Wenceslaus and the royal crypt in St Vitus Cathedral at Prague Castle, Czech Republic. For the most part, the fabrics correspond to contemporary classifications of Asian and Middle Eastern textiles and, with the exception of two, they were woven using the lampas technique from pure silk. Fabric patterns were woven with a main liseré weft, a silk pattern weft in various colours and a pa􀆩 ern metal weft, typically from a gilded strip of an animal substrate. Plant patterns dominate, in some cases accompanied by animals, geometric elements and inscriptions in Arabic script. Most of the fabrics were made in the 13th and 14th centuries. While the origin of one of the fabrics can be traced directly to northern China, the majority was woven in central Asia or northern China, with a smaller number in central Asia or the Middle East. The interpretation of the assemblage demonstrates the wealth of the medieval court and church dignitaries under the Přemyslid and Luxembourg rulers at Prague Castle which enabled them to acquire these highly luxurious goods from distant lands.